2019
DOI: 10.1002/jcb.29316
|View full text |Cite
|
Sign up to set email alerts
|

miR‐496 remedies hypoxia reoxygenation–induced H9c2 cardiomyocyte apoptosis via Hook3‐targeted PI3k/Akt/mTOR signaling pathway activation

Abstract: The hypoxia‐reoxygenation (H/R) model helps analyze myocardial infarction triggered by acute myocardial ischemia, which induces cardiomyocyte proliferation and apoptosis. The Gene Expression Omnibus database was used to obtain the GSE74205 and GSE3866 microarray data, including microRNA (miRNA) and messenger RNA profiles, to catalog potential key miRNAs and genes. The role of rno‐mir‐496 expression in cardiomyocyte proliferation within 10 days of birth was established. The microRNA Target Prediction Database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…*P < .005 vs SR group cardiovascular diseases via the above signaling pathways. 35 In addition, AF can lead to a wide range of abnormalities, including changes in the local myocardial microenvironments, inflammatory responses, mitochondrial dysfunction, abnormal lipid metabolism, and further facilitate the initiation and maintenance of AF, [36][37][38] meanwhile, the enrichment analysis in this experiment has also confirmed the role of miRNAs in the formation of mechanisms of AF via the above mechanisms. Therefore, miRNAs in the serum are able to participate in the formation of mechanisms of AF through various factors, and meanwhile, the results of this enrichment analysis can provide research directions for further exploring the specific mechanisms of miRNAs affecting the initiation of AF.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…*P < .005 vs SR group cardiovascular diseases via the above signaling pathways. 35 In addition, AF can lead to a wide range of abnormalities, including changes in the local myocardial microenvironments, inflammatory responses, mitochondrial dysfunction, abnormal lipid metabolism, and further facilitate the initiation and maintenance of AF, [36][37][38] meanwhile, the enrichment analysis in this experiment has also confirmed the role of miRNAs in the formation of mechanisms of AF via the above mechanisms. Therefore, miRNAs in the serum are able to participate in the formation of mechanisms of AF through various factors, and meanwhile, the results of this enrichment analysis can provide research directions for further exploring the specific mechanisms of miRNAs affecting the initiation of AF.…”
Section: Discussionmentioning
confidence: 61%
“…Jin et al also found that miR‐496 was able to remedy hypoxia‐induced cardiomyocyte apoptosis via PI3k/Akt/mTOR signaling pathways. The above demonstration indicated that MAPK and mTOR signaling pathways play an essential role in the progression of cardiovascular diseases, and at the same time, various miRNAs inside human body play significant a role in the progression of cardiovascular diseases via the above signaling pathways 35 . In addition, AF can lead to a wide range of abnormalities, including changes in the local myocardial microenvironments, inflammatory responses, mitochondrial dysfunction, abnormal lipid metabolism, and further facilitate the initiation and maintenance of AF, 36‐38 meanwhile, the enrichment analysis in this experiment has also confirmed the role of miRNAs in the formation of mechanisms of AF via the above mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, miRNAs play an important role in the regulation of stem cell osteogenic differentiation. Aberrant expression of miR-125a-5p has been observed in various diseases, including myocardial infarction (Jin and Ni, 2019), atherosclerosis (Hu et al, 2019), cerebral injury (Yao et al, 2019), diabetes (Rubie et al, 2019), and various malignant tumors (Mason et al, 2018;Ma et al, 2019;Wang et al, 2019). Inhibition of miR-496 has been found to reverse the inhibitory effects of IL-1β in bone marrow stem cell-associated bone regeneration (Huang and Chen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study on myocardial infarction in rats indicated that increased expression of miR-133a can reduce the mRNA and protein levels of TGF-β1 and CTGF after myocardial infarction, decreasing myocardial collagen deposition, inhibiting myocardial fibrosis and improving heart function [6]. In addition, a study suggested that miR-496 is able to resist myocardial apoptosis by targeting Hook3 and activating the phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR signaling pathway [7].…”
Section: Introductionmentioning
confidence: 99%